Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning di Kelas V Sekolah Dasar - Rohima, Aisyatur; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The purpose of this study was to describe the improvement of integrated thematic learning process by using the Problem Based Learning model in class V of SDN 05 Puhun Pintu Kabun. This type of research is Class Action Research (CAR) using a qualitative and quantitative approach. The research subjects were teachers and 27 grade V students of SDN 05 Puhun Pintu Kabun, Bukittinggi City. The use of the Problem Based Learning model in the learning process can improve student learning outcomes. This can be seen from the results of the RPP assessment in the first cycle obtaining an average percentage of 81.94% (B), in the second cycle it was 94.44% (A). Assessment of teacher aspects in the first cycle obtained an average percentage of 81.25%, and increased in the second cycle to 90.62%.Assessment of aspects of students in the first cycle obtained an average percentage of 79.68% (C), in the second cycle to 90.62% (A). Based on these results it can be concluded that using the Problem Based Learning model can improve the learning process. <w:Lsd